Opportunities and challenges in lifelong learning and continuing professional development among nurses at a cancer hospital in Sri Lanka - Hirushi Kawya Munasinghe; Kodippili Arachchige Vathmi Shavenka Suraweera; Weerakkody Appuhamilage Dineth Harshan Weerakkody; Ukwattage Dona Hiruni Kanchana; Faiz Mohideen Mohamed Thassim Marikar (Belitung Raya Foundation, 2023)
Background: Continuing Professional Development (CPD) and lifelong learning are essential for nurses to keep up to date with innovations, technological enhancements, and development in the healthcare sector to improve patient outcomes and safety. Objective: The study aimed to identify platforms, awareness, and barriers to CPD and lifelong learning of nursing professionals at Cancer Hospital (Apeksha), Maharagama, Sri Lanka. Methods: A quantitative survey was conducted, and a self-administered questionnaire was used to collect samples from April 2022 to February 2023. Random sampling techniques were used to select the samples from the population of nurses. The study sample size was 235, and only 200 nurses responded. Results: Descriptive statistics were calculated, and cross-tabulations were also employed. The nursing professionals in the study setting are characterized by a significant gender imbalance, with most nurses being female (86.5%) and males comprising a minority (13.5%). Most nurses have one to five years of experience, with just over a third (37.5%) having between one to ten years of experience. Family responsibilities, poor physical health, and financial constraints were identified as the most common barriers to engaging in CPD. Workplace stress, lack of financial aid, lack of opportunities, leave issues, inflexible work hours, and workload at the ward/unit were the most commonly agreed-upon organizational barriers in CPD. Despite various channels for accessing CPD activities, including colleagues and the workplace, a significant proportion of respondents were not aware of opportunities and platforms through these channels, highlighting the need for increased awareness and accessibility of CPD opportunities. Conclusion: CPD is crucial for nurses to grow their careers and improve their knowledge and abilities. Main obstacles such as family obligations, financial restraints, and occupational stress must be overcome to motivate nurses to engage in CPD activities and foster professional progress. There should be a proper mechanism to increase the awareness of CPD among nurses.